New Early Cretaceous palaeomagnetic and geochronological results from the far western Lhasa terrane: Contributions to the Lhasa-Qiangtang collision. Issue 1 (December 2017) - Bian, Weiwei; Yang, Tianshui; Ma, Yiming; Jin, Jingjie; Gao, Feng; Zhang, Shihong; Wu, Huaichun; Li, Haiyan
Abstract To better constrain the Lhasa- Qiangtang collision, a combined palaeomagnetic and geochronological study of the far western Lhasa terrane was conducted on the Duoai Formation lava flows ( 113–116 Ma), as well as on the Early Cretaceous Jiega Formation limestone. Following detailed rock magnetic, petrographical, and palaeomagnetic experiments, characteristic remanent magnetisation directions were successfully isolated from most samples using principal component analysis. The tilt-corrected direction groups yielded a palaeopole at 69.1°N, 319.8°E with A95 = 4.8° (N = 19). A primary origin for the magnetisation is consistent with positive fold tests. Our results from the Early Cretaceous units, combined with published palaeomagnetic data obtained from Cretaceous strata from the Lhasa and western Qiangtang terranes, show that these two terranes had already collided by the Early Cretaceous, the Lhasa terrane had a relatively east-west alignment, and it remained at a relatively stable palaeolatitude during the entire Cretaceous. Comparing the Cretaceous palaeolatitude calculated for the western Lhasa terrane with those from Eurasia and Mongolia suggests a latitudinal convergence of 1400 ± 290 km and 1800 ± 300 km, respectively, since the Early Cretaceous.